Spolno kazensko pravo - Korošec, Damjan (Podjetje in delo, 2016)
The author stresses some anomalies in the system and errors in the Slovenian sexual criminal law. He mainly points out several combinations of offender's and victim's sex, directness and victimocentricity of sexual acts in the criminal code, the offender's possession of arms as an aggravated circumstance of a sexual offence, praeterintentional result in sexual crime and the whole system of levels of unlawfulness of interpersonal sexual actions.
Keywords: kazensko pravo; kazniva dejanja; Slovenija; spolna zloraba; spolno nadlegovanje; spolno nasilje